Synthesis and preliminary in vitro evaluation of DOTA-Tenatumomab conjugates for theranostic applications in tenascin expressing tumors. Issue 15 (1st August 2019) - Giannini, Giuseppe; Milazzo, Ferdinando Maria; Battistuzzi, Gianfranco; Rosi, Antonio; Anastasi, Anna Maria; Petronzelli, Fiorella; Albertoni, Claudio; Tei, Lorenzo; Leone, Loredana; Salvini, Laura; De Santis, Rita
Graphical abstract: Abstract: Tenatumomab is an anti-tenascin murine monoclonal antibody previously used in clinical trials for delivering radionuclides to tumors by both pre-targeting (biotinylated Tenatumomab within PAGRIT) and direct 131 Iodine labeling approaches. Here we present the synthesis and in vitro characterization of three Tenatumomab conjugates to bifunctional chelating agents (NHS-DOTA, NCS-DOTA and NCS-DTPA). Results indicate ST8198AA1 (Tenatumomab-DOTAMA, derived by conjugation of NHS-DOTA), as the most promising candidate in terms of conjugation rate and yield, stability, antigen immunoreactivity and affinity. Labeling efficiency of the different chelators was investigated with a panel of cold metals indicating DOTAMA as the best chelator. Labeling of Tenatumomab-DOTAMA was then optimized with several metals and stability performed confirms suitability of this conjugate for further development. ST8198AA1 represents an improvement of the previous antibody forms because the labeling with radionuclides like 177 Lu or 64 Cu would allow theranostic applications in patients bearing tenascin expressing tumors.